Strategies to develop a prophylaxis for the prevention of HPA-1a immunization and fetal and neonatal alloimmune thrombocytopenia. (February 2020) - Kjær, Mette; Geisen, Christof; Akkök, Çiğdem Akalın; Wikman, Agneta; Sachs, Ulrich; Bussel, James B.; Nielsen, Kaspar; Walles, Katarina; Curtis, Brian R.; Vidarsson, Gestur; Järås, Kerstin; Skogen, Bjørn
Abstract: Anti-HPA-1a-antibodies are the main cause of fetal and neonatal alloimmune thrombocytopenia (FNAIT) which may result in intracranial hemorrhage (ICH) and death among fetuses and newborns. Advances in understanding the pathogenesis of FNAIT and proof of concept for prophylaxis to prevent immunization suggest that development of hyperimmune anti-HPA-1a IgG aimed at preventing immunization against HPA-1a and FNAIT is feasible. Anti-HPA-1a IgG can be obtained either by isolating immunoglobulin from already-immunized women or by development of monoclonal anti-HPA-1a antibodies. Here we discuss recent advances that may lead to the development of a prenatal and postnatal prophylactic treatment for the prevention of HPA-1a-associated FNAIT and life-threatening FNAIT-induced complications.